The Epidemiology of Plant Diseases - COOKE, B.M.; JONES, D. GARETH; KAYE, BERNARD; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2006)
Plant disease epidemiology is a dynamic science that forms an essential part of the study of plant pathology. This book brings together a team of 35 international experts. Each chapter deals with an essential component of the subject and allows the reader to fully understand how each exerts its influence on the progress of pathogen populations in plant populations over a defined time scale. Since the first edition of the text was published in 1998, many new developments have occurred in the subjects covered, particularly molecular diagnostics, modelling, fungicide resistance and information technology. The second edition of the book is a comprehensive text on all aspects of plant disease epidemiology that should serve as an invaluable reference work for those involved in this fascinating science of crop plants.
Principles and Methods -- Plant disease diagnosis -- Disease assessment and yield loss -- Surveys of variation in virulence and fungicide resistance and their application to disease control -- Infection strategies of plant parasitic fungi -- Epidemiological consequences of plant disease resistance -- Dispersal of foliar plant pathogens: mechanisms, gradients and spatial patterns -- Pathogen population dynamics -- Modelling and interpreting disease progress in time -- Disease forecasting -- Diversification strategies -- Epidemiology in sustainable systems -- Information technology in plant disease epidemiology -- Case Examples -- Seedborne diseases -- Diseases caused by soil-borne pathogens -- Wind-dispersed diseases -- Environmental biophysics applied to the dispersal of fungal spores by rain-splash -- Potato late blight -- Apple scab: role of environment in pathogen and epidemic development -- Onion diseases -- The recent epidemic of cassava mosaic virus disease in Uganda.
Keywords: LIFE SCIENCES; BOTANY; PLANT DISEASES; LIFE SCIENCES; PLANT PATHOLOGY; PLANT SCIENCES